Kebutuhan Keluarga Pasien Kritis Berdasarkan Jenis Kelamin - Muhammad Luthfi Muflih; Sri Rahayu (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2026)
Introduction: Families of patients suffering from critical illnesses in the Intensive Care Unit (ICU) commonly experience emotional distress, uncertainty, and complex information needs. Gender differences significantly impact the responses of families to critical illness, with women typically showing more emotional involvement and a greater psychological burden than their male counterparts.Objectives: To identify differences in the needs of family members of critically ill patients based on genderMethods: This study, which is cross-sectional and quantitative in nature, explored the needs of 100 family members (50 males and 50 females) of patients receiving care in the ICU at Moewardi Hospital. Data collection was conducted through purposive sampling, employing a validated Indonesian version of the Critical Care Family Needs Inventory (CCFNI). Due to the non-normal distribution of the data, gender-based differences were analyzed using the Mann-Whitney test, with proportional sampling techniques applied to ensure group balance.Results: Women exhibited higher average scores on all subscales of the Critical Care Family Needs Inventory (CCFNI) in comparison to men. Notable differences were identified in the proximity, assurance, family support, and information subscales (p < 0.001), as well as in the comfort subscale (p = 0.032). These results indicate that women have greater emotional, informational, and environmental comfort needs when accompanying critically ill patients.Conclusions: Gender significantly influences the needs of family members of critically ill patients, with women consistently showing elevated levels of need across all domains of the CCFNI. These findings underscore the importance of implementing gender-sensitive, family-centered care strategies to improve the quality of critical care services.